Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar IPAS Siswa Kelas IV SDIT Al Akhyar - Hasanah, Hani Saripatun; Megawati, Megawati; Agrita, Tri Wera (CV. Master Literasi Indonesia, 2025)
This research is in the background of students' low problem-solving ability so that it affects their learning outcomes because educators have not used technology-based learning models and media. The purpose of this study is to analyze the influence of the Problem Based Learning (PBL) learning model on the learning outcomes of social studies of grade IV students at SDIT Al Akhyar. The research method used was an experiment with the research design of Pre-Group Pretest-Posttest Design type. The sample of this study consisted of 18 IVA class students who were taken using random sampling techniques. The instrument used in this study is a cognitive test consisting of multiple-choice questions and essay questions. The data analysis technique used in this study is a t-test (Paired simple t-test) with the result of tcount > ttable, namely 9.492 > 2.110 with sig (2-tailed) < α 0.05, meaning that Ha is accepted and H0 is rejected. Therefore, it can be concluded that there is an influence of the Problem Based Learning (PBL) model on the learning outcomes of IPAS students in grade IV of SDIT Al Akhyar.